2009
DOI: 10.2136/vzj2008.0061
|View full text |Cite
|
Sign up to set email alerts
|

Winter Hydrologic and Erosion Processes in the U.S. Palouse Region: Field Experimentation and WEPP Simulation

Abstract: Soil erosion by water is detrimental to soil fertility, crop yield, and the environment. For cold areas, knowledge of winter hydrologic processes is critical to determining land‐use and management practices for reducing soil loss and protecting land and water resources. Adequate understanding of winter processes is also essential to developing models as effective predictive tools. This study evaluated the effects of two contrasting tillage practices on winter hydrologic and erosion processes, and the suitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…This is consistent with the findings of Stadler et al (2000), who demonstrated the preferential flow of water through macropores in a frozen soil column by conducting dye tracing experiments in a controlled laboratory. Because soil tillage disturbs the continuity of the macropore network, agricultural fields under conventional tillage tend to have lower frozen‐soil infiltration capacity than fields under no‐till management (e.g., Singh et al, 2009). Therefore, it is important to better understand the functions of macropores in frozen soil and to effectively represent them in existing models of water and heat transfer (Stähli et al, 1996).…”
Section: Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Stadler et al (2000), who demonstrated the preferential flow of water through macropores in a frozen soil column by conducting dye tracing experiments in a controlled laboratory. Because soil tillage disturbs the continuity of the macropore network, agricultural fields under conventional tillage tend to have lower frozen‐soil infiltration capacity than fields under no‐till management (e.g., Singh et al, 2009). Therefore, it is important to better understand the functions of macropores in frozen soil and to effectively represent them in existing models of water and heat transfer (Stähli et al, 1996).…”
Section: Hydrologymentioning
confidence: 99%
“…Freeze–thaw reduces soil cohesive strength and aggregate stability (see above) and consequently increases soil erodibility following thawing of the surface soil. Rainfall or snowmelt on a thawed, bare soil (e.g., after fall cultivation) overlying a solid frozen layer can cause high rates of erosion because the thawed soil has a high water content that reduces its mechanical strength and the subsurface frozen layer impedes infiltration and generates overland flow (Singh et al, 2009). Rills may form on the thawed soil surface, which can substantially increase erosion rates.…”
Section: Mechanical Processesmentioning
confidence: 99%
“…As total numbers of seedlings did not differ between the seed mats, there are no strong indications that many seeds moved out of the seed mat or that differences between snow and rain simulations are due to differences in viability. The low dispersal capacity of snow is in line with the minimal erosion because of snowmelt observed in non-tillage plots by Singh et al (2009) but in apparent contradiction with the calculated erosion by snow by Sukhanovskii (2008). However, the latter included soils that were tilled and subjected to quite large volumes of water.…”
mentioning
confidence: 52%
“…The low dispersal capacity of snow is in line with the minimal erosion because of snowmelt observed in non‐tillage plots by Singh et al . () but in apparent contradiction with the calculated erosion by snow by Sukhanovskii (). However, the latter included soils that were tilled and subjected to quite large volumes of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation